Characterization of a bacteriocin as biopreservative synthesized by indigenous lactic acid bacteria from dadih soya traditional product used in West Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Retnaningrum E, Yossi T, Nur'azizah R, Sapalina F, Kulla PDK. 2020. Characterization of a bacteriocin as biopreservative synthesized by indigenous lactic acid bacteria from dadih soya traditional product used in West Sumatra, Indonesia. Biodiversitas 21: 4192-4198. A total of 4 isolates of lactic acid bacteria (strain BDL08, BDL11, BDL12, and BDL13) isolated from dadih soya were investigated for the ability to produce bacteriocin based on their antibacterial activities against Listeria monocytogenes ATCC 7644. Based on comparative 16S rDNA sequencing analysis, isolates BDL 11, BDL12, and BDL13 were identified as Lactobacillus plantarum while the isolates BDL 08 was identified as Leuconostoc mesenteroides. All crude bacteriocins producing strains revealed broad antibacterial spectrum against 7 different indicator bacteria, including Gram-positive and Gram-negative bacteria. L. plantarum BDL11 displayed the highest bacteriocin activity relative to others. The bacteriocin produced by the strain was not affected by pH, heating, and NaCl concentration but was sensitive to proteolytic enzymes. This research indicated that the bacteriocin in the food industry has the potential to be used as a biopreservative.
Keywords: Antibacterial activities, food industry, Lactobacillus plantarum, proteolytic enzyme, 16S rDNA